2010
DOI: 10.1111/j.1600-9657.2010.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental trauma in individuals with special needs

Abstract: The present data suggest that DT prevalence in individuals presenting special needs is more common in permanent dentition and that the first attendance by a dental surgeon is delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 20 publications
5
47
3
1
Order By: Relevance
“…15,16 Correlations between TDI and the medical condition showed that there was a statistically significant relationship between TDI and intellectual disabilities as well as visual and hearing impairments. 15,16 Correlations between TDI and the medical condition showed that there was a statistically significant relationship between TDI and intellectual disabilities as well as visual and hearing impairments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Correlations between TDI and the medical condition showed that there was a statistically significant relationship between TDI and intellectual disabilities as well as visual and hearing impairments. 15,16 Correlations between TDI and the medical condition showed that there was a statistically significant relationship between TDI and intellectual disabilities as well as visual and hearing impairments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lip incompetence significantly increased the risk of TDI (P=.009). 7,9,10,15,16 This indicates the need to further investigate the varying barriers to dental care in CSHCN, including economics, numbers of trained and willing practitioners, parent and caregiver awareness, problems in transportation, and negative thoughts related to oral health care. 21,22 Regarding the treatment sought, only 27.7% of the study group had previously sought treatment for TDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have implicated not only lack of awareness but also economic & social factors [2,3]. Also first attendance by a dental surgeon is delayed [13].…”
Section: Discussionmentioning
confidence: 99%
“…6 The prevalence of intellectual disability among children is 0.3-0.8%, but the prevalence of traumatic injuries in children with intellectual disability is about 20-30%. This may be attributed to epilepsy, which is very common in children with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%